Drug use and nightlife: more than just dance music - Broekaert Eric; Lammertyn Jan; Vanderplasschen Wouter; Van Havere Tina; Bellis Mark (BMC, 2011)
Abstract Background Research over the last decade has focused almost exclusively on the association between electronic music and MDMA (3,4-Methylenedioxymethamphetamine or "ecstasy") or other stimulant drug use in clubs. Less attention has been given to other nightlife venues and music preferences, such as rock music or southern/funky music. This study aims to examine a broader spectrum of nightlife, beyond dance music. It looks at whether certain factors influence the frequency of illegal drug and alcohol use: the frequency of going to certain nightlife venues in the previous month (such as, pubs, clubs or goa parties); listening to rock music, dance music or southern and funky music; or sampling venues (such as, clubs, dance events or rock festivals). The question of how these nightlife variables influence the use of popular drugs like alcohol, MDMA, cannabis, cocaine and amphetamines is addressed. Methods The study sample consisted of 775 visitors of dance events, clubs and rock festivals in Belgium. Study participants answered a survey on patterns of going out, music preferences and drug use. Odds ratios were used to determine whether the odds of being an illegal substance user are higher for certain nightlife-related variables. Furthermore, five separate ordinal regression analyses were used to investigate drug use in relation to music preference, venues visited during the last month and sampling venue. Results Respondents who used illegal drugs were 2.5 times more likely to report that they prefer dance music. Goa party visitors were nearly 5 times more likely to use illegal drugs. For those who reported visiting clubs, the odds of using illegal drugs were nearly 2 times higher. Having gone to a pub in the last month was associated with both more frequent alcohol use and more frequent illegal substance use. People who reported liking rock music and attendees of rock festivals used drugs less frequently. Conclusions It was concluded that a more extended recreational environment, beyond dance clubs, is associated with frequent drug use. This stresses the importance of targeted prevention in various recreational venues tailored to the specific needs of the setting and its visitors.